Use of MAP Yemen by the government, development partners and academics: towards more effective allocation of development funding - CGIAR Research Program on Policies, Institutions, and Markets (2019)
MAP Yemen is a comprehensive online database on food and nutrition security projects and related Sustainable Development Goal and other development indicators. Its launch in 2018 was considered a milestone towards more coordinated and evidence-based project and policy planning in Yemen. The database builds the knowledge of the government, development partners, researchers and other interested parties on the state of the country’s food and nutrition security in order to foster effective allocations of funds and synergies.